Tax competition and the determination of the quality of public goods - A. H. Abdessalam (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
In this paper, the author analyzes the behavior of local governments in capital taxation when the financial choices in terms of the quality of public goods are made done by a central planner. More specifically, he asks the question of whether a local government has an interest in taxing the mobile factor in addition to the tax on representative households. Through a comparison of social welfare given the strategies chosen by local governments, the author shows that whatever the quality and cost of public goods, a local government always has an interest in taxing the mobile factor. This leads to a Nash equilibrium in the dominant strategy in their model.
Keywords: D00; H20; H41; H70; 330; Tax competition; public goods; quality; welfare; taxation